Acid Phosphatase and Zinc Tests Are Effective for Semen Examination and Identification to Prove Intercourse - Yudianto, Ahmad; Wibowo, Ariyanto; Nuraini, Indah; Aung, Htet Htet (Folia Medica Indonesiana, 2020)
The presence of spermatozoa in vagina is a definite sign of sexual intercourse. However, sometimes microscopic examination does not find spermatozoa or reveals a false negative result. This is influenced by many factors, including the absence of ejaculate in the vaginal canal. In addition, there are other factors such as oligo/azoospermia, vasectomy, degeneration of sperm due to time, incorrect sampling, and improper storage. Therefore, examination of the other components of the ejaculate, ie. the enzyme acid phosphatase, choline and spermin, is important. Compared with spermatozoa, the enzyme phosphatase, choline and spermin have lower evidentiary value because these three components are less specific. However, the level of phosphatase enzyme found in the vagina is much lower than phosphatase enzyme that comes from prostate gland. In this study, as many as 192 samples in the form of patches with sperm/semen stains were tested with acid phosphatase test and zinc test through direct and indirect examination. In the first method, washing was carried out on day 1, day 7, and month 3, and testing was carried out after each washing. In the second method, washing was carried out simultaneously and testing was carried out on day 1, day 7 and month 3. Washing was carried out using 7 types of detergent for each 4 patch samples, and washing using water as control. The results showed very low sensitivity (0.186) and very high specificity (100%). This showed that both tests had high specificity values. Acid phosphatase test specifically showed the presence of the enzyme phosphatase, while zinc test specifically showed the presence of zinc in semen. This phosphohydrolase-phosphatase enzyme is easily degraded due to external factors, including temperature, humidity, and chemicals, ie. the element SDS (Sodium Dodecyl Sulfate) that has the ability to cut enzymes. The weakness of the acid phosphatase test is that this enzyme is easily degraded, either partially or completely, due to external factors, such as temperature, humidity, heat, and the presence of chemicals.